Hydrothermally synthesized CuxO as a catalyst for CO oxidation. Issue 7 (21st February 2015) - Guo, Mu Yao; Liu, Fangzhou; Tsui, Jenkin; Voskanyan, Albert A.; Ng, Alan Man Ching; Djurišić, Aleksandra B.; Chan, Wai Kin; Chan, Kwong-Yu; Liao, Changzhong; Shih, Kaimin; Surya, Charles
<x xml:space="preserve">Abstract</x> Hydrothermally synthesized CuxO exhibited improved performance for CO oxidation compared to the hydrothermally synthesized Cu2O, as well as commercial CuO nanoparticles.